Kulturindustri og sikkerhedsstat. To noter om kritikken af The Wire og en om ”Dread Pirate Roberts” - Jensen, Erik Granly (K&K - Kultur og Klasse, 2016)
The central question in this article concerns the current state of critique at the threshold of the digital age of surveillance. How is it in other words possible to respond critically within this new paradigm of the security state, and where should we look to further develop such a possible critical approach? The HBO TV-series The Wire is at the center of this article, due to its focus on surveillance and communication technologies. The overall focus, however, is to follow the critical readings of the series by Slavoj Žižek and Fredric Jameson. Both Žižek and Jameson frame their analysis by insisting on the political implications of the cultural industries. Furthermore, it is a central claim in the present article that it is not possible any longer (maybe it never was possible) to distinguish the infrastructure of the cultural industries from the infrastructure of the security state. For this reason, the analysis is primarily concerned with the inseparability of the communication technologies, the cultural industries and the security state; and the thesis is that a contemporary critique needs to address this infrastructural problem in the midst of our mediated society.